Administrative Leadership Behaviours of Principals of Colleges of Education and their Impact on Tutors’ Job Performance in the Volta Region, Ghana - Pajibo, Edison; Dzikunu, Cosmos Kwame; Asare, Mercy Obesebea (American Journal of Education and Learning, 2019)
This study examined the administrative leadership behaviours employed by principals of colleges of education in the Volta Region of Ghana and their relationship with tutors’ job performance. The study employed a cross-sectional descriptive survey design using the quantitative approach. Adopting the multi-stage sampling technique, 160 participants participated in the study. All 6 principals were purposively sampled while 154 tutors were selected through a combination of stratified and random sampling techniques. A structured questionnaire was used for data collection. The study revealed that democratic leadership behaviour (M=3.30, SD=0.86) was dominant among the principals while the autocratic leadership behaviour (M=2.34, SD=0.94) was least practiced in the colleges. The study also discovered that gender, age, academic qualification and years of experience significantly affected tutors and principals’ behaviours. It was also revealed that tutors’ level of job performance was very good and that there was a positive correlation between principals’ leadership behaviours and tutors’ job performance. Therefore, it was recommended that the National Council for Tertiary Education (NCTE), through Colleges of Education (CoE) should organize in-service training for the principals to enable them to balance the use of leadership behaviours in specific situations. The study concluded that good leadership practices engender good tutor performance.